The difference in biofilms formations on duration less than 90 d and more than 90 d of tracheotomy cannula usage - Pradhana Fajar Wicaksana; Dian Paramita Wulandari; Angga Kusuma; Siswanto Sastrowijoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Currently, prevention of local and systemic infections caused by implantable devices is increasingly improved. Tracheostomy is a surgical action followed by an implantable device called tracheotomy cannula into a trachea to maintain upper airway patenting. The incidence of biofilm-related complications and infections is associated with the length of duration of the attached tracheostomy. The formation and spread of biofilms from distal cannula increase the infection incidence in stoma, tracheitis, and even peripheral pneumonia. However, until now there has been no consensus on when the tracheostomy replacement supposedly conducted. Some manufacturers recommend that cannula replacement supposedly conducted within 30 d, but the data are not yet in agreement and need further study. This study aimed to determine the difference in biofilms formations in a duration of less than 90 d and more than 90 d of tracheotomy cannula usage. It was a cross-sectional study involving patients who underwent a tracheostomy at the Department of Otorhinolaryngology of Dr. Sardjito General Hospital, Yogyakarta. Fisher exact test was applied to analyze the biofilms formations of the two different duration of tracheostomy cannula usage. A total of 20 patients were involved in this study.  Durations of more than 90 d had more biofilms formations compared to less than 90 d, although it was not significantly different (p>0.05). However, the PR value of 6 indicated that subjects who have attached cannula more than 90 d clinically have 6 times higher risk for developing biofilms formations than those less than 90. In conclusion, there is no significant differences in biofilms formations between the less than 90 d and more than 90 d of tracheostomy cannula usage. However, clinically subjects with longer duration of tracheostomy cannula usage have higher risk for developing biofilms formations.